A Systematic Literature Review of Total Quality Management (TQM) Implementation in Organization - Aprillia Susmita (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
Technic Quality Management concepts and ideas are formalized based on the foundation of work carried out over the last few centuries, Quality management begins with a simple inspection-based system, where a product is compared against product standards by a team of inspectors. The purpose of this research is to find out how the TQM principles are implemented in various industrial sectors in improving all components of the company. In this study, we reviewed 40 TQM papers published between 2011 and 2020. The method used is to review research papers that discuss companies implementing Technic Quality Management. A total of 27 journals (about 68%) used the implementation of TQM and 13 journals (32%) as review methods. From these results it can be seen that 74% of companies that implement TQM use survey data sources and 26% of companies use other data. Finally, this paper shows that every TQM implementation contains at least one of the eight TQM principles, namely leadership, involvement of people, process approach, system approach management, continuous improvement, factual approach to decision making, mutual beneficial supplier relationships, customer-focused organization.